Mental Process Found in Donald Trumph’s Speech on Covid 19: Systemic Functional Linguistic Approach - Meriyanti; Nurlela; Muhammad Yusuf (Talenta Publisher, 2023)
This research deals with mental process were found in Donald Trumph’s speech. Mental process was used to express people’s feeling, thinking, perceiving shows other desire toward things in life. With these mental productions, humans can express their view, ideas, and a feeling to public through speech. As in Donald Trump’s speech on his presidential speech in addressing the outbreak of COVID-19 in his country. The language used in his speech determines the success of communication with the participant since language express speaker feeling, idea and desire. This research was conducted by using descriptive qualitative research. The data were obtained from Donald Trumph’s speech and source of the data were the script of Donald Trump’s speech on March 11, 2020 about the coronavirus. The data were collected by documentary sheet. The data analysis used interactive model by Miles, Huberman, and Saldana. The findings show that 1) there were 39 utterances that contained of mental process were found in Donald Trumph’s speech, namely 17 (43.6%) for cognition, 11 (28.2%) for desiderative, 7 (17.9%) for affection, and 4 (10.3%) for perception. The highest type of mental process in Donald Trumph’s speech was cognition. It means that Trumph provided his insight to American people about the corona virus in order to make them to be calm in facing the outbreak. It reflected the way of he logically thinks.